2015
DOI: 10.2118/173315-pa
|View full text |Cite
|
Sign up to set email alerts
|

Oil-Rate Forecast by Inferring Fractional-Flow Models From Field Data With Koval Method Combined With the Capacitance/Resistance Model

Abstract: Many empirical and analytical models were developed to forecast oil production. Empirical models (including data-driven models) can, for example, find correlations between oil cut and production, but they lack explicit knowledge of the physical behavior. Classic analytical models are loyal to reservoir physics. Nevertheless, they often require estimation of water saturation as a function of time, which is difficult to obtain for multiwell reservoirs. It is desirable to combine advantages of both empirical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 11 publications
0
23
0
1
Order By: Relevance
“…Moreover, the Koval water fractional-flow equation developed by Cao et al (2014Cao et al ( , 2015 is applied to separate the oil production from total production. Thereafter, a novel ensemble-based optimization framework preconditioning hybrid nonlinear constraints is then provided to minimize the squared difference between the predicted and observed production data, so that the interwell geological parameters such as connectivity coefficients, time constants, and drained pore volumes will be eventually estimated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the Koval water fractional-flow equation developed by Cao et al (2014Cao et al ( , 2015 is applied to separate the oil production from total production. Thereafter, a novel ensemble-based optimization framework preconditioning hybrid nonlinear constraints is then provided to minimize the squared difference between the predicted and observed production data, so that the interwell geological parameters such as connectivity coefficients, time constants, and drained pore volumes will be eventually estimated.…”
Section: Methodsmentioning
confidence: 99%
“…By history matching field water cut data, two characteristic parameters, the Koval factor and drainage volume, are estimated, which takes the form of Eq. (8) (Cao et al, 2014(Cao et al, , 2015.…”
Section: Koval Fractional-flow Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Holanda et al [19] further introduced the state-space (SS) theory to describe the dynamic behavior of CRMs as a multi-input/multi-output system. Capacitance-resistance models were also incorporated with fractional flow models [20,21] to allow the prediction of oil rates. It indicated that the Koval model proposed by Cao et al [21] may not be a good choice for mature waterfloods, but it is effective enough to revisit abrupt breakthroughs caused by active aquifer support, which widely exist in karst carbonate reservoirs.…”
mentioning
confidence: 99%
“…Capacitance-resistance models were also incorporated with fractional flow models [20,21] to allow the prediction of oil rates. It indicated that the Koval model proposed by Cao et al [21] may not be a good choice for mature waterfloods, but it is effective enough to revisit abrupt breakthroughs caused by active aquifer support, which widely exist in karst carbonate reservoirs. During production of karst reservoirs, large-scale fractured-vuggy units are usually treated as isolated targets for continuous waterflood, thereby the previous CRM models should be modified to supply the aquifer influx rate as needed with all contributing injection rates.Owing to the fact that understanding reservoir fluid dynamics to achieve optimal decision-making by grid-based reservoir models is computationally expensive and frequently require large volumes of uncertain data to estimate petrophysical properties, full field-scale models are not easy for rapid reservoir analysis to make reliable decisions.…”
mentioning
confidence: 99%